SOCIALIZING PROJECT BASED LEARNING METHOD IMPLEMENTATION FOR PRIMARY SCHOOL TEACHERS IN JAKARTA PROVINCE IN INDONESIA - Zulela Zulela; Arifin Maksum; Arita Marini; Desy Safitri; Sujarwo; Nurzengky Ibrahim (Bajang Institute, 2022)
Location of this international collaboration of community service is in the Province of Jakarta in Indonesia. The target of this community service is elementary school teachers in the Province of Jakarta in Indonesia. The problem with the target audiences is that the competences in applying Project Based Learning method of primary school teachers in the Province of Jakarta in Indonesia has not been managed properly and their interests in implementing Project Based Learning method are still low. In addition to this, the socialization of Project Based Learning method for Primary School Teachers in Jakarta Province in Indonesia has not been done before. In order to develop the competences of applying Project Based Learning method for Primary School Teachers in Jakarta Province in Indonesia to enhance student creativity and innovation at primary schools in the province of Jakarta in Indonesia, the solution is socialization of applying Project Based Learning method for them